BACTERIAL DIVERSITY OF THE DEEP SEA OF SANGIHE TALAUD, SULAWESI - Gintung Patantis; Ekowati Chasanah; Dewi Seswita Zilda; Ikhsan B. Waluyo (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2012)
Deep sea is an extreme environment characterized by cold temperature, high pressure, lackof light and nutrients. Microorganisms live in these habitat are unique microorganisms andknown to have tremendous source of potential agents for biotechnology processes. Indonesia asan archipelagic country has a vast deep ocean. This study aims to see the diversity of bacteria inSangihe Talaud Deep Sea, Sulawesi. Analysis of bacterial diversity was carried out by culturedand uncultured method. Terminal Restriction Fragment Length Polymorphism (T-RFLP) techniquewas used for uncultured analysis of the microorganisms biodiversity, while cultured one wasdone by plating the samples of water onto Zobell media. The results showed that, there were 21isolates obtained by cultured method. The identification which based on 16S rDNA by PCR methodshowed the genus of Pseudomonas, Pseudoalteromonas, Alteromonas, Vibrio, Shewanella andUncultured bacterium were identified. However, 14 classes of bacteria were obtained by usingTRFLP method i.e Acetobacteraceae class, Actinobacteria, α-proteobacteria, -proteobacteria, δ-proteobacteria, γ-proteobacteria, Bacili, Bacteroidetes, Chlorobi, Chroococcales, Clostridia,Erysipelotrichi, Synergistia, and Zetaproteobacteria. here were also unclassified bacteria anduncultured bacterium found in the samples.